2016
DOI: 10.11138/jts/2016.4.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Rockwood grade I and II acromioclavicular injuries: as benign as commonly believed?

Abstract: Abstractthe acromioclavicular (AC) joint is the articulation between the distal clavicle and the acromion process of the scapula. As the upper limb moves, passive motion of the AC joint occurs in three planes, with the AC and coracoclavicular ligaments providing stability. injuries are common, particularly during contact sports, and are classified using Rockwood's system. Grade i (sprain) and ii (rupture) injuries only affect the AC ligaments and are generally managed conservatively. However, recent reports ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…When Fukuda studied the anatomy and function of the acromioclavicular joint, it was found that the coracoclavicular ligament maintains the vertical stability of the acromioclavicular joint, and the conical ligament and the trapezoidal ligament are opposite in opposing forces and maintain a balance [ 10 ]. Klassen conducted research and analysis on the ligaments around the acromioclavicular joint and found that the acromioclavicular joint complex was the strongest, followed by the tapered ligament, and the trapezoid ligament the weakest [ 11 ]. The detailed anatomical structure and biomechanical research provide sufficient basis for the treatment of acromioclavicular joint dislocation that is not rigidly fixed, elastic, and more in line with anatomy and human biomechanics [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When Fukuda studied the anatomy and function of the acromioclavicular joint, it was found that the coracoclavicular ligament maintains the vertical stability of the acromioclavicular joint, and the conical ligament and the trapezoidal ligament are opposite in opposing forces and maintain a balance [ 10 ]. Klassen conducted research and analysis on the ligaments around the acromioclavicular joint and found that the acromioclavicular joint complex was the strongest, followed by the tapered ligament, and the trapezoid ligament the weakest [ 11 ]. The detailed anatomical structure and biomechanical research provide sufficient basis for the treatment of acromioclavicular joint dislocation that is not rigidly fixed, elastic, and more in line with anatomy and human biomechanics [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study indicated that conservative treatment is usually used for patients with Rockwood classification I and II [ 10 , 11 , 12 ]. When the acromioclavicular joint dislocation is of Rockwood type III and above, the acromioclavicular ligament and the coracoclavicular ligament are completely broken, causing shoulder pain and restriction of activities, thereby seriously affecting the daily activities of patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nonsteroidal anti-inflammatory drugs, immobilization, physical therapy), but several studies have reported poor long-term outcomes in terms of pain and disability. 15 , 16 , 17 In 2003, Mouhsine et al. 17 evaluated 33 patients with grade I and II AC separations treated by conservative measures, including ice application, analgesics, and immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…nonsteroidal anti-inflammatory drugs, immobilization, physical therapy), but several studies have reported poor long-term outcomes in terms of pain and disability. [15][16][17] In 2003, Mouhsine et al 17 evaluated 33 patients with grade I and II AC separations treated by conservative measures, including ice application, analgesics, and immobilization. The authors reported 27% of patients (9 of 33; 7 grade II and 2 grade I) failing conservative treatment and requiring subsequent surgery an average of 26 months after injury.…”
Section: Discussionmentioning
confidence: 99%